2023
DOI: 10.1111/cpr.13441
|View full text |Cite
|
Sign up to set email alerts
|

Zonula occludens‐1 distribution and barrier functions are affected by epithelial proliferation and turnover rates

Abstract: Zonula occludens‐1 (ZO‐1) is a scaffolding protein of tight junctions, which seal adjacent epithelial cells, that is also expressed in adherens junctions. The distribution pattern of ZO‐1 differs among stratified squamous epithelia, including that between skin and oral buccal mucosa. However, the causes for this difference, and the mechanisms underlying ZO‐1 spatial regulation, have yet to be elucidated. In this study, we showed that epithelial turnover and proliferation are associated with ZO‐1 distribution i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…This hypothesis is supported by a study that describes ZO-1 redistribution in an early phase of physiologic cell shedding during intestinal cellular renewal process ( Guan et al, 2011 ). Consistently, a recent study has shown that the distribution/localization of ZO-1 can be altered during cell turnover or proliferation ( Imafuku et al, 2023 ). Other independent studies have revealed that ZO-1 can be localized in the nuclei and can regulate gene expression ( Balda et al, 2003 , Balda and Matter, 2000 , Zhong et al, 2012 ).…”
Section: Discussionsupporting
confidence: 68%
“…This hypothesis is supported by a study that describes ZO-1 redistribution in an early phase of physiologic cell shedding during intestinal cellular renewal process ( Guan et al, 2011 ). Consistently, a recent study has shown that the distribution/localization of ZO-1 can be altered during cell turnover or proliferation ( Imafuku et al, 2023 ). Other independent studies have revealed that ZO-1 can be localized in the nuclei and can regulate gene expression ( Balda et al, 2003 , Balda and Matter, 2000 , Zhong et al, 2012 ).…”
Section: Discussionsupporting
confidence: 68%
“…S100 calcium binding protein A4 (S100A4) impacts cytoskeletal dynamics and motility and is crucial for the migratory aspects of EMT ( 183 ). ZO-1 contributes to cell adhesion and polarity through its role in tight junctions ( 184 ).…”
Section: Epithelial-mesenchymal Transitionmentioning
confidence: 99%
“…No. ab221547) using primary antibodies (Abcam) diluted at 1:200, as described previously [10,18,20]. The ImageJ software was used to measure the area of fluorescence on at least four images for each EpiSkin specimen using a fixed threshold.…”
Section: Haematoxylin-eosin (He) and Immunofluorescence Stainingmentioning
confidence: 99%